Affect as methodology: Feminism and the politics of emotion - Åhäll, Linda (International Political Sociology, 2018)
International relations scholars are increasingly paying attention to “the emotional” as a way to understand global politics. What is often missing from these conversations is feminist knowledge on affect, and also discussions about methodology. By presenting a feminist methodological approach to the affective-discursive to analyze the politics of emotion, this paper aims to fill this gap. It starts by discussing feminist critiques of the “affective turn.” Then, a methodological framework of gender, discourse, and affect as a structure that “goes-without-saying” is presented. Hemmings’ concept of affective dissonance is used as a tool guiding a feminist curiosity, useful to zoom in on the political puzzle of what emotion (in its broadest sense) does. The third section draws on two examples of being emotional about violent “Woman” to illustrate how moments of affective dissonance spark a feminist curiosity about gender, agency, and political violence. In conclusion, the paper argues that feminist knowledge on affect offers a way to re-tune, reset, and reimagine research on the politics of emotion. By prioritizing affect as methodology, feminist knowledge should be valuable for critical endeavors interested in changing the status quo, no matter if the political puzzle is about gender or not.
Keywords: corps; discipline; genre; histoire et politique; méthodologie; relations internationales; ressource en ligne; science politique; science politique et droit; sciences humaines; sociologie; thématiques; violences; émotions